2017
DOI: 10.1016/j.cherd.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Droplet deformation under pulsatile electric fields

Abstract: Highlights  Drop deformation dynamics under pulsatile electric fields is analysed.  A good quantitative agreement with experimental data is obtained.  The effects of electrical and physical parameters are quantified.  Results are compared with a linear model of the same process.  The ratio of Weber number and Ohnesorge number describes droplet deformation well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 43 publications
3
5
0
1
Order By: Relevance
“…It is remarkable that the optimal frequency of 100 Hz obtained in the current case (see shows decreasing coalescence efficiency at high frequencies. Interestingly, it can also be seen from this figure that the frequency range 60-200 Hz, where the pulsatile electric fields perform better than the constant fields, is the same as that where a non-linear relationship of the deformation ratio versus the ratio of Weber Number and Ohnesorge Number is observed [20]. Another noteworthy point is that the sawtooth waveform has proved to perform best at the high conductivity of 3 g L -1 and low residence times (2 and 3s) among the pulsatile fields.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…It is remarkable that the optimal frequency of 100 Hz obtained in the current case (see shows decreasing coalescence efficiency at high frequencies. Interestingly, it can also be seen from this figure that the frequency range 60-200 Hz, where the pulsatile electric fields perform better than the constant fields, is the same as that where a non-linear relationship of the deformation ratio versus the ratio of Weber Number and Ohnesorge Number is observed [20]. Another noteworthy point is that the sawtooth waveform has proved to perform best at the high conductivity of 3 g L -1 and low residence times (2 and 3s) among the pulsatile fields.…”
Section: Discussionsupporting
confidence: 52%
“…Notwithstanding a number of research works [14][15][16][17][18][19] conducted on the effect of the electric waveform on electrocoalescence, the understanding of the influence of the waveforms is still limited, with some contrasting conclusions. Lundgaard et al [16] and Lesaint et al [17] ranked the efficiency of AC waveforms as square > sinusoidal > triangular, which is similar to the results obtained by Li et al [20]; whereas Mousavi et al [15] reported that the coalescence efficiency of pulsed DC triangular and halfsinusoidal waves was superior to that obtained with square waves. Flat electrodes were used in the work of Lundgaard et al [16] and Mousavi et al [15], while cylindrical electrodes were used in the work of Lesaint et al [17].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…[11][12][13] Electric dehydration has the advantages of high dehydration efficiency and quality, but it can only work at low moisture content with a complex power supply. [14][15][16] Overall, a large amount of energy or chemicals is consumed during oil-water treatment. Therefore, it is highly desired to develop a sustainable and efficient method for separating oil-water emulsions.A triboelectric nanogenerator (TENG) can instantly convert environmental energy into electricity and then serves as an energy harvester, active sensor portable power sources, and self-powered systems.…”
mentioning
confidence: 99%